IMPLEMENTASI PRINSIP KEADILAN TERHADAP GURU DARI PERSPEKTIF HUKUM: ANALISIS KEBIJAKAN DAN PERLINDUNGAN HUKUM DALAM SISTEM PENDIDIKAN INDONESIA - Umar Iskandar; Darni Asis; M. Ersyad Indrapraja; Muhammad Idris Tahir; Rahmat J (Journal of Innovation Research and Knowledge, 2024)
Teachers hold a strategic role in fostering a high-quality education system in Indonesia. Through Law Number 14 of 2005 on Teachers and Lecturers and Law Number 20 of 2003 on the National Education System, the government has demonstrated its commitment to ensuring teachers’ welfare, legal protection, and opportunities for professional development. However, the practical implementation of these fundamental rights often falls short, particularly for non-civil servant teachers and those serving in remote areas. Significant gaps persist between the normative provisions and the realities on the ground, especially regarding welfare, legal protection, and professional development opportunities. This study employs a qualitative methodology with a juridical-normative approach to evaluate the effectiveness of implementing justice principles for teachers in Indonesia. Data were gathered through interviews and document analysis. The findings reveal notable disparities in the realization of justice principles, primarily driven by limited regional budgets, low levels of legal literacy, and insufficient governmental support. The study recommends increasing budget allocations, enhancing awareness of teachers' legal rights, and implementing stricter oversight mechanisms to ensure policy compliance. This research provides an in-depth analysis of the challenges faced by teachers in accessing their rights and highlights the urgent need for more equitable policies to improve the welfare and protection of the teaching profession.